The Role of Organizational Policy Communication: Supporting Disaster Mitigation Management in Gorontalo, Indonesia - Aneta, Yanti; Nusi, Djefriyanto; Anggrayni, Yenny; Solihin, Dwi Indah Yuliani; Hulinggi, Pebriyanto A. (Journal Public Policy, 2024)
Policies will be implemented well when communication is carried out by implementing transmission communication, consistency, and clarity. The research examines the topic of policy communication in flood disaster mitigation efforts in Gorontalo, Indonesia. The research uses a qualitative approach with an inductive mindset, this research starts from field data regarding the implementation of flood mitigation policies in Gorontalo Regency. The results of the study show that 1) Transmission communication has been carried out by various communication methods, such as apples, coordination meetings, socialization, and dialogue forums, used to disseminate information about flood mitigation policies; 2) Clarity of information shows that stakeholders are trying to ensure that the public understands information about flood disaster mitigation and is able to take appropriate steps when disasters occur; 3) Consistency of information related to disaster mitigation policies, scheduled evaluation practices, participation of community leaders, implementation of coordination meetings, and prevention of leadership dualism are crucial elements carried out by stakeholders. Based on the previous description, policy communication not only focuses on transmission, consistency, and clarity of information in flood mitigation, but must also be adaptive. Governments need to adapt communication to local cultures, values, and situations to ensure policies are more relevant and accepted by the community. The strength of this research is the comprehensive mapping of communication strategies in flood mitigation policies, identifying methods of internal government communication and socialization to the community. This provides a better understanding of the delivery and reception of information. The limitation is that it focuses only on disaster mitigation, so the findings are only relevant for disaster mitigation studies.